Comparability in Opportunistic Behavior - Staniec, Iwona (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
The article is a review and based on the study of practices used to measure opportunism. The targeted selection was used in this paper. The purpose of the paper is to present the tools for measuring the phenomenon of opportunism used in empirical research. Research results indicate that there is no single accepted tool for measuring this phenomenon. However – which is important from the point of view of replicability of these studies – obtained values of measurement of the phenomenon of opportunism indicate that its intensity is low. In all approaches, opportunism is treated as a multidimensional construct in which the number of dimensions and the way of measuring each of them can be different.